Perception of Academicians towards Quality of Public Service Marketing in Pokhara - Palikhe, Amin (Nepalese Journal of Public Affairs, 2023)
This study mainly focuses on understanding user perception and experiences towards quality of public service marketing on delivery by using the five service delivery dimensions: accessibility, cost, time, barrier and behavior. The research methodology comprises descriptive research design followed by stratified simple random sampling for permanent academic faculty members under multi stage sampling from one constitute and four affiliated college. The primary sources of data were collected through semi structure questionnaire method. Reliability and validity were tested. The study reveals that overall qualities of public service delivery dimension are moderate. The academicians were satisfied with the quality of public service delivery in Pokhara but perception was not as expected. However, the qualitative result depicted that there were major challenges in service delivery such as problem from staff, risk after payment of fees and extra efforts for completing lengthy service. In addition, environmental situation, employees’ attitude, intermediaries, and Afno Manche (known person), salary level and political interventions cause changes in behavior during public service delivery. So, public service institutions should give due attention to such issues to improve quality of service delivery. Even though there is no specific model to measure the quality of public service delivery in Nepalese context therefore, a CAT-Behavior model is recommended for measuring the quality of public service delivery in Nepalese context and it could be beneficial from different perspective.